Subjective Bond Returns and Belief Aggregation - Buraschi, Andrea; Piatti, Ilaria; Whelan, Paul (Review of Financial Studies, 2022)
Abstract This paper proposes an aggregation scheme of subjective bond return expectations based on the historical accuracy of professional interest rate forecasters. We use disaggregated survey data on bond returns and document large disagreement in the cross-sectional distribution and persistence in forecast accuracy. Our aggregate subjective belief proxy outperforms equal weighting schemes, and its dynamics are significantly different from statistical forecasting models. With this measure in hand, we study the relationship between quantities of risk and subjective expectations of excess returns and demonstrate a strong link between the two, even if such a relationship is difficult to detect using realized returns. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.